Hydrogels Containing o-Nitrobenzyl Ester at Cross-Linking Points: Soft Matters for Fabrication of Functionalizable Microwells - Turanli, Aleyna; Demirbilek, Nisa; Gevrek, Tugce N. (Amer Chemical Soc, 2023)
Light-responsive o-nitrobenzyl ester-containing poly-(ethylene glycol)-based hydrogel was synthesized via a nucleophilic Michael addition reaction, both as bulk gel and as a film on the glass surface. Obtained hydrogels were thoroughly characterized using Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), and scanning electron microscopy (SEM). Because of the presence of the photodegradable o-nitrobenzyl ester units, the hydrogels underwent degradation upon ultraviolet (UV) irradiation, yielding the amine-reactive nitroso-benzaldehyde groups at the newly formed interface. The photogenerated nitroso-benzaldehydes were further functionalized with amine-containing molecules, as proved by FTIR analysis. Additionally, the hydrogels were applied as films on glass surfaces, enabling patterned photodegradation by using photomasks with circular patterns. SEM analysis confirmed hydrogel etching and formation of microwells induced by UV irradiation. To assess the immobilization of bioactive ligands within the microwells, protein immobilization was performed. Fluorescence microscopy analysis demonstrated specific biofunctionalization exclusively within the microwells, while nonspecific adsorption was absent in the remaining parts of the hydrogel due to the antifouling nature of the PEG units. We believe that the reported hydrogel can be useful for applications that involve bioimmobilization.
Keywords: light-responsive hydrogels; photopatterning; microwells; o-nitrobenzyl ester; aldehyde-amine coupling